MODELS OF FALSE AND CORRECT DETECTION OF INFORMATION LEAKAGE SIGNALS FROM MONITOR SCREENS BY A SPECIALIZED TECHNICAL MEANS OF ENEMY INTELLIGENCE - Yevgrafov, Dmytro; Yaremchuk, Yurii (Informatyka, Automatyka, Pomiary w Gospodarce i Ochronie Środowiska, 2024)
The calculation expressions for the probability of false detection of a leakage signal, taking into account the discrete representation of time in the models of detection of side radiation signals from static images on the monitor screen on liquid crystal structures by a specialised technical means of enemy intelligence, which implements an asymptotically optimal joint algorithm for detecting side radiation signals and estimating the duration of the image on the monitor screen, are refined. For this purpose, a large independent array of noise was generated in the Mathcad software environment, and the process of false signal detection by a specialised enemy intelligence vehicle was modelled in several Excel workbooks under conditions of a priori uncertainty about the duration of a static image on the monitor screen.